2017
DOI: 10.1111/ajt.14038
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Urinary Microbiome Populations Correlate in Kidney Transplants With Interstitial Fibrosis and Tubular Atrophy Documented in Early Surveillance Biopsies

Abstract: An unbalanced microbiome may lead to disease by creating aberrant immune responses. A recent association of cellular rejection with the development of interstitial fibrosis and tubular atrophy (IFTA) suggests the role of immune-mediated tissue injury. We hypothesized that developing IFTA correlates with altered urinary tract microbiomes (UMBs). UMBs at two serial time points, 1 and 6-8 months post-transplant, were assessed by 16S microbial ribosomal gene sequencing in 25 patients developing biopsy-proven IFTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 45 publications
2
92
0
Order By: Relevance
“…Lee et al investigated kidney transplant recipients found to have AR but the authors examined the gut microbiome rather than urine. The work of Modena et al studied the urinary microbiome as a marker for kidney allograft dysfunction, but all of these patients had already developed the irreversible changes of IFTA (scored moderate to severe by 2007 Banff criteria). Based on index biopsy data, the prevalence of moderate to severe IFTA in our cohort was less than in Salomon's cohort (see Table ); greater than 80% of our allograft biopsies (cases as well as controls) were scored at 0 or 1 by Banff criteria for interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lee et al investigated kidney transplant recipients found to have AR but the authors examined the gut microbiome rather than urine. The work of Modena et al studied the urinary microbiome as a marker for kidney allograft dysfunction, but all of these patients had already developed the irreversible changes of IFTA (scored moderate to severe by 2007 Banff criteria). Based on index biopsy data, the prevalence of moderate to severe IFTA in our cohort was less than in Salomon's cohort (see Table ); greater than 80% of our allograft biopsies (cases as well as controls) were scored at 0 or 1 by Banff criteria for interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several Corynebacterium species are known skin and mucosal commensals, and others are known to cause urinary tract infections, but the significant incidence increase in cases suggests their presence is due to more than simple contamination. All patients were instructed by study coordinators on proper clean‐catch technique for urine sampling, and this would have minimized skin flora contamination as in other urine microbiome studies with similar outlined protocols . Our study initially set out to identify both bacterial and fungal signatures in the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations